2011
DOI: 10.1121/1.3523300
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation and flight strategy of Japanese house bats during natural foraging, revealed by a microphone array system

Abstract: Using only a microphone array system, echolocation pulses and three-dimensional flight paths in the frequency-modulated bat, Pipistrellus abramus, during natural foraging, were simultaneously examined. During the search phase, the inter-pulse interval, pulse duration, and moving distance of the bat between successive emissions were relatively constant at around 89.5 ± 18.7 ms, 6.90 ± 1.31 ms, and 0.50 ± 0.20 m, respectively. The bats started to decrease these acoustical parameters within 2-3 m of the prey capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…abramus during natural foraging emits long (9-11 ms) shallowsweeping frequency-modulated (FM) sounds, with energy concentrated in the terminal sweep frequency of the fundamental component around 40 kHz (15,25). The bat decreases the pulse duration and interpulse interval (IPI) while approaching target prey (16,30) and slightly extends the constant-frequency (CF) portion of the pulse just before approaching a prey item (16). When the bat successfully captures an insect, it completes the interception with an easily recognized brief burst of sounds emitted at a high rate of about 150 Hz (the "feeding buzz"), followed by a silent interval (the "postbuzz pause") (31).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…abramus during natural foraging emits long (9-11 ms) shallowsweeping frequency-modulated (FM) sounds, with energy concentrated in the terminal sweep frequency of the fundamental component around 40 kHz (15,25). The bat decreases the pulse duration and interpulse interval (IPI) while approaching target prey (16,30) and slightly extends the constant-frequency (CF) portion of the pulse just before approaching a prey item (16). When the bat successfully captures an insect, it completes the interception with an easily recognized brief burst of sounds emitted at a high rate of about 150 Hz (the "feeding buzz"), followed by a silent interval (the "postbuzz pause") (31).…”
Section: Methodsmentioning
confidence: 99%
“…The model assumes two prey items, because the microphone-array measurement showed that bats sometimes capture two prey items consecutively and rarely capture more than two insects within short time intervals. Bats changed their flight paths much more acrobatically in the horizontal plane than in the vertical plane during natural foraging (15,16). Thus, we separately model flight dynamics in the horizontal and vertical planes as follows:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations